In vitro evaluation of antibacterial activity of Annona squamosa Linn leaf extract against Escherichia coli - goh, vonny (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2024)
Background. Escherichia coli is normal bacterial flora that located in the lower gastrointestinal tract. Most of Escherchia coli strains are harmless, however some of them can cause mild infection until severe life-threatening complication. Recently, it has been reported that rapidly rising antibiotics resistance on this bacteria because the relatively high use of antibiotics. Therefore, new innovations are needed to reduce the increasing number of antibiotic resistant bacteria. One of them is by using medicinal plants that has antimicrobial activity. Flavonoids, alkaloids, tannins, and terpenoids contents on Annona squamosa L. leaf extract have been proved potentially as antibacterial. Objectives. This study aimed to evaluate the potential activity of Annona squamosa L. ethanolic leaf extract against the growth of Escherichia coli bacteria. Methods. This is an experimental laboratory study using the agar well diffusion method in the Microbiology Laboratory, Faculty of Medicine, University of North Sumatra. The fresh leaves of Annona squamosa L. were extracted by maceration method using the 96% ethanol. The various concentration of the extract (6.25%, 12.5%, 25%, and 50%) were added to Muller Hinton agar that already applied with 24-hours old culture of Escherichia coli ATCC 25922, with gentamicin as positive control and DMSO as negative control. Results. The diameters of the inhibition zone with concentrations of 6.25%, 12.5%, 25%, 50% Annona squamosa L. leaf extract consecutively 5,525 0,450 mm, 6,275 0,350 mm, 6,525 0,471 mm, 7,925 1,072 mm. Conclusion. In conclusion, the ethanolic leaf extract of Annona squamosa L. has antibacterial activity against Escherichia coli.